Emotion processing differences mediate the link between sex and autistic traits in young adulthood - Lucy A. Livingston; Lucy H. Waldren; Esther Walton; Punit Shah (Wiley, 2022)
Abstract Background The male preponderance in autism diagnoses is widely reported, yet the psychological mechanisms (e.g., emotion processing) underlying this sex difference are poorly understood. Contributing to this gap in knowledge, most research has not been designed to investigate the intermediary (i.e., mediating) role of psychological processes in the relationship between sex and autism. Compounding this issue, concerns that autism measures are not reliably measuring the same constructs in males and females, and bias against females in clinical samples, make it difficult to investigate the psychological mechanisms underlying sex differences in autism. Methods Over two cross‐sectional studies, 1656 young adults from the general population reported their sex (as assigned at birth) and completed questionnaires indexing their emotion processing differences, as well as a measure of autistic traits suggested to tap into the same psychometric construct in males and females. Results Emotion processing differences mediated the relationship between sex and autistic traits, whereby being male was associated with more emotion processing differences, which were subsequently linked with greater levels of autistic traits. There remained a direct effect of sex on autistic traits after accounting for emotion processing differences. Conclusions Emotion processing differences are a potential psychological mechanism underpinning higher prevalence of autism in males, which may serve a compensatory function in females; for example, females may seek out emotion‐inducing experiences to help compensate for social‐emotional difficulties. These findings inform our understanding of autism‐related sex differences and have potential implications for clinical practice, where the need for sex‐specific support and diagnostic processes is increasingly being recognised.